(untitled) (Quinto Sol, 2022)
The emergence and spread of HIV/aids was a global phenomenon that began in the 1980’s and was swiftly incorporated into journalistic agendas. Argentina’s print media was no exception. Through the description and analysis of articles on the subject published in Argentine newspapers and magazines from that decade, it is observed how a gradual appearance turned, since 1985, into an overabundance of scarcely hierarchized news, with a profusion of voices with various degrees of relevance and contradictory messages, which generated an information chaos. At the same time, there is an examination of the representations that these media outlets put in circulation, their changes, and the sensationalistic ways of reporting on the new virus and the new disease.